Asas dan Implementasi: Pendidikan Agama Kristen Ditinjau dari Perspektif Yohanes Calvin - Rezeki Putra Gulo (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
This article uses a library approach; Review and analyze actual facts from the Bible, articles, and books as reference material. This effort aims to review Calvin's contribution to Christian Religious Education. The background of this research is that there are not a few Christian Religion teachers today who still don't understand what Calvin's contributions to PAK are. Referring to this problem, some of Calvin's contributions regarding the principles and implementation of Christian Religious education that must be known by PAK teachers, namely: Definition of PAK, PAK Objectives, PAK Students, PAK Educators, and PAK Curriculum. The final conclusion of this study is that Christian religion teachers really need the five principles of applying PAK to become educators who are capable of teaching.